The Relationship between Portunidae Diversity and Mangrove Density at Popongan Coastal Baluran National Park, East Java Indonesia - Dewi, Yuni Kartika; Purnomo, Hari; Sudarmadji, Sudarmadji (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2017)
This research was conducted in the mangrove forest of Popongan beach at Baluran National Park, East Java. The aim of this research was to determine the relationship between mangrove density and Portunidae diversity in mangrove forest at Popongan beach. Line transect method was used in this research. There are three transects consist of 17 plots, each plot sized 20m x 20m. The data analysis were done by using Person correlation and linear regression R Program. The results showed p-value 0,003, it means there is relationship between Portunidae diversity and the mangrove density. The temperature and tide showed p-value < 0,005, that means the abiotic factors affect Portunidae diversity in mangrove. The Portunidae diversity at mangrove forest of Popongan beach is relatively low (H’value 0,152). There were five species was found, there were Charybdis (Charybdis) miles, Podhopthalmus vigil, Portunuspelagicus,Scyllaserrata,and Thalamita crenata. The dominant species in this mangrove forest is Thalamita crenata. The composition of mangrove forest vegetation were Rhizophora apiculata, Ceriops tagal, Lumnitzera racemosa, Rhizophora stylosa, Sonneratia alba, Bruguiera gymnorrhiza, Pemphis acidula, dan Xylocarpus moluccensis. The dominant vegetation in this mangrove forest is Rhizophora apiculata.